(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
Nano zero valent iron (nZVI) is often used in the remediation of organic and inorganic contaminant and has been hailed as an emerging remediation tool. Unfortunately, were few studies has been done on the toxicity of nZVI on organisms especially aquatic organisms. In this study, the toxicity of commercial forms (uncoated, organic coating, and iron oxide coating) of nano zero-valent iron (nZVI) to the marine phytoplankton Isochrysis galbana is revisited in terms of the determination of the EC50 or median effective concentration using nonlinear regression. Based on the four-parameter logistics equation, the median effective concentration for Nanofer 25S, Fe2+ and Fe3+ were 5.46 mg/L (95% confidence interval of 4.84 to 6.16), 70.89 mg/L (95% confidence interval of 37.26 to 134.9), 64.29 mg/L (95% confidence interval of 44.92 to 92.02). The results indicate that Nanofer 25S was the most toxic.